2017
DOI: 10.1093/gastro/gox016
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis Endoscopic Index of Severity (UCEIS) versus Mayo Endoscopic Score (MES) in guiding the need for colectomy in patients with acute severe colitis

Abstract: BackgroundThe Ulcerative Colitis Endoscopic Index of Severity (UCEIS) and the Mayo Endoscopic Score (MES) were developed as an objective method of the endoscopic severity in ulcerative colitis (UC); however, it was still unclear whether UCEIS vs MES could guide the need for colectomy in acute severe colitis (ASC).MethodsConsecutive ASC patients between January 2012 and May 2016 were retrospectively evaluated. Demographic data, previous therapy, clinical observations, laboratory parameters, medical therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 22 publications
2
63
0
3
Order By: Relevance
“…All patients underwent ileocolonoscopy, after which the CDEIS scores for CD and UCEIS scores for UC were calculated by experienced physicians to determine endoscopic activity . Endoscopically active disease was defined as CDEIS >3 for CD and UCEIS >1 for UC . The Montreal classification was used to categorise the location and behaviour of the disease …”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent ileocolonoscopy, after which the CDEIS scores for CD and UCEIS scores for UC were calculated by experienced physicians to determine endoscopic activity . Endoscopically active disease was defined as CDEIS >3 for CD and UCEIS >1 for UC . The Montreal classification was used to categorise the location and behaviour of the disease …”
Section: Methodsmentioning
confidence: 99%
“…Disease activity among patients with UC was assessed using the UC endoscopic index of severity (UCEIS), Mayo endoscopic score (MES) and Mayo score/disease activity index for UC (Mayo/DAI) [35][36][37]. Disease severity in patients with Crohn's disease was assessed using simple endoscopic score (SES-CD), the Crohn's disease activity index (CDAI) and the Harvey Bradshaw index (HBI) [37][38][39]. According to the latest ECCO guidelines, clinical indices should be carefully used since they are not well-validated in the clinical practice and discrepancies could be seen [34].…”
Section: Assessment Of Disease Severitymentioning
confidence: 99%
“…Recent studies have shown a potential advantage of using the UCEIS scoring system, with 1 study showing improved accuracy of the UCEIS score in predicting the need for colectomy compared with the Mayo Score, with score greater than 7 showing a sensitivity of 60.3% with a specificity of 85.5%. 98 Another study showed that a UCEIS score of 5 or more was associated with a 50% chance of requiring rescue therapy and 33% rate of colectomy compared with 27% and 9% for those with a score of less than or equal to 4. As mentioned previously, the commonly used Oxford (or Travis) index, developed in 1996, predicted the need for colectomy to be 85% in patients with a CRP level greater than 45 mg/L and 3 to 8 bowel movements a day after 3 days of IVCS treatment.…”
Section: Introductionmentioning
confidence: 99%